Burning Rate Enhancement Analysis of End-Burning Solid Propellant Grains Based on X-Ray Real-Time Radiography. (22nd June 2020) - Xianggeng, Wei; Tao, Bo; Pengbo, Wang; Xinjian, Ma; Yongchun, Lou; Jian, Chen
Abstract : Unexpected pressure rise may occur in the end-burning grain solid rocket motor. It is generally believed that this phenomenon is caused by the nonparallel layer combustion of the burning surface, resulting in the increase of burning rate along the inhibitor. In order to explain the cause of this phenomenon, the experimental investigation on four different end configurations were carried out. Based on the X-ray real-time radiography (RTR) technique, a new method for determining the dynamic burning rate of propellant and obtaining the real-time end-burning profile was developed. From the real-time images of the burning surface, it is found that there was a phenomenon of nonuniform burning surface displacement in the end-burning grain solid rocket motor. Through image processing, the real-time burning rate of grain center line and the real-time cone angle are obtained. Based on the analysis of the real-time burning rate at different positions of the end surface, the end face cone burning process in the motor working process is obtained. The closer to the shell, the higher the burning rate of the propellant. Considering the actual structure of this end-burning grain motor, it is speculated that the main cause of the cone burning of the grain may be due to the heat conduction of the metal wall. By adjusting the initial shape of the grain end surface, the operating pressure of the combustion chamber can be basically unchanged, so as to meet the mission requirements. The results show that the method can measure the burning rate of solid propellant in real time and provide support for the study of nonuniform combustion of solid propellant.